Clinical outcomes after ACL reconstruction in soccer (football, futbol) players: A systematic review and meta-analysis - Hong, I. S.; Pierpoint, L. A.; Hellwinkel, J. E.; Berk, A. N.; Salandra, J. M.; Meade, J. D.; Piasecki, D. P.; Fleischli, D. P.; Ahmad, C. S.; Trofa, D. P.; Saltzman, B. M. (Sports Health: A Multidisciplinary Approach, 2023)
Context: The risk factors for anterior cruciate ligament (ACL) tear for athletes participating in pivoting sports includes young age and female sex. A previous meta-analysis has reported a reinjury rate of 15% after ACL reconstruction (ACLR) for athletes across all sports. To the best of the authors` knowledge, this is the first systematic review and meta-analysis of available literature reporting outcomes after ACLR in soccer players.